Analisis Pembiayaan Program Promotif dan Preventif Pemberantasan Demam Berdarah Dengue (DBD) Bersumber Pemerintah di Kota Semarang Tahun 2013-2015 - Kamila, Nisa; Nadjib, Mardiati (Jurnal Ekonomi Kesehatan Indonesia, 2017)
In 2010–2014, Semarang was involved as the big three city with high incidence rate of dengue in Central Java province. This study aimed to analyze the financing by the local government for Dengue preventive program in 2013-2015, as well as the resources gap. The health account approach was used to analyze spending by source, function, and provider. Total local government spending for dengue in 2013 were IDR 4.018.927.020,- increased by 101% in 2014 and increased by 218% in 2015. The largest expenditure for Dengue Preventive program is epidemiological surveillance and infectious disease control. There was no gap between available resources and requires program according to SPM. The study suggested to improve planning by focusing on the direct activities such as promotive and preventive